2023
DOI: 10.3390/biomedicines12010041
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Training after Spinal Cord Injury Affects Brain Structure and Function: From Mechanisms to Methods

Le-Wei He,
Xiao-Jun Guo,
Can Zhao
et al.

Abstract: Spinal cord injury (SCI) is a serious neurological insult that disrupts the ascending and descending neural pathways between the peripheral nerves and the brain, leading to not only functional deficits in the injured area and below the level of the lesion but also morphological, structural, and functional reorganization of the brain. These changes introduce new challenges and uncertainties into the treatment of SCI. Rehabilitation training, a clinical intervention designed to promote functional recovery after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 189 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…Currently, there are many studies supporting a potential role for post-synaptic plasticity in encouraging axonal regeneration and recovery. Notably, recent studies have shown that following SCI, electrical stimulation can significantly increase the growth and branching of axons via upregulation of axon growth-and regeneration-promoting genes and factors, which also contributes to induction of Hebbian www.nature.com/scientificreports/ plasticity 46,47 . Furthermore, previously "silent" (NDMA-only) synapses have been found to undergo activation and reorganization in the face of electrical stimulation, which has been proposed to be a potential mechanism for rejuvenating neural pathways via encouragement of post-injury synaptic plasticity and axonal regrowth 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are many studies supporting a potential role for post-synaptic plasticity in encouraging axonal regeneration and recovery. Notably, recent studies have shown that following SCI, electrical stimulation can significantly increase the growth and branching of axons via upregulation of axon growth-and regeneration-promoting genes and factors, which also contributes to induction of Hebbian www.nature.com/scientificreports/ plasticity 46,47 . Furthermore, previously "silent" (NDMA-only) synapses have been found to undergo activation and reorganization in the face of electrical stimulation, which has been proposed to be a potential mechanism for rejuvenating neural pathways via encouragement of post-injury synaptic plasticity and axonal regrowth 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that physical exercises can reverse or prevent disruptions in GABAergic and glycinergic regulation, increasing the expression of glutamate decarboxylase 67 (GAD67), glycine receptor (GlyR), and gamma-aminobutyric acid subtype A (GABAA) in the lower thoracic Th10 and lumbar L2 segments [42], via BDNF-TrkBdependent pathways in SCI [43]. It has been shown that interneurons with increased expression of GAD67, GlyR, and GABAA play a role in locomotion, as they can modify the pace of the stepping cycle, and their reduction post-SCI may lead to prolonged activation of spinal motoneurons [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews focus on the effects of rehabilitation in patients with SCIs. Indeed, He et al present a review of the effects of physical exercise on the reorganization of communication between the brain and the spinal cord, while Stanciu et al describe the reported effects of rehabilitation through hydrotherapy [28,29].…”
mentioning
confidence: 99%